Tungsten-disulphide-based heterojunction photodetector - Ahmad, Harith; Rashid, Haroon; Ismail, Mohammad Faizal; Thambiratnam, Kavintheran (Optical Society of America, 2019)
Two-dimensional (2D) materials have realized significant new applications in photonics, electronics, and optoelectronics. Among these materials is tungsten disulphide (WS2), which is a 2D material that shows excellent optoelectronic properties, tunable/sizable bandgap in the visible range, and good absorption. A polycrystalline WS2 thin film is successfully deposited on a substrate using radio frequency magnetron sputtering at room temperature. The x-ray diffraction pattern reveals two hexagonal structured peaks along the (100) and (110) planes. Energy-dispersive x-ray spectroscopy reveals a non-stoichiometric WS2 film with 1.25 ratio of S/W for a 156.3 nm thick film, while Raman shifts are observed at the E1 2g and A1g phonon modes located at 350.70 cm−1 and 415.60 cm−1, respectively. A sandwiched heterojunction photodetector device is successfully fabricated and illuminated within the violet range at 441 nm and 10 V of bias voltage. The maximum photocurrent values are calculated as 0.95 μA, while the responsivity is observed at 169.3 mA W−1 and detectivity 1.48 × 108 Jones at illuminated power of 0.6124 μm. These results highlight the adaptability of the present technique for large-scale applications as well as the flexibility to promote development of advanced optoelectronic devices. © 2019 Optical Society of America.